2015
DOI: 10.1016/j.jtcme.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Crocus sativus L. (saffron) for cancer chemoprevention: A mini review

Abstract: Cancer is one of the most feared diseases globally and there has been a sustained rise in its incidence in both developing and developed countries. Despite the growing therapeutic options for patients with cancer, their efficacy is time-limited and non-curative. Hence to overcome these drawbacks, an incessant screening for superior and safer drugs has been ongoing for numerous decades, resulting in the detection of anti-cancer properties of several phytochemicals. Chemoprevention using readily available natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(64 citation statements)
references
References 46 publications
1
61
0
2
Order By: Relevance
“…[53] Assignment into 13 groups to receive: (1) normal saline, (2) paraffin, (3) diazepam (3 mg/kg), (4-7) saffron aqueous extracts at different doses (56, 80, 320 and 560 mg/kg, respectively), (8)(9)(10) crocin at different doses (50,200 and 600 mg/kg), (11-13), [11][12][13] safranal at different doses (0.05, 0.15, 0.35 ml/kg, respectively).…”
Section: Anxiety and Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…[53] Assignment into 13 groups to receive: (1) normal saline, (2) paraffin, (3) diazepam (3 mg/kg), (4-7) saffron aqueous extracts at different doses (56, 80, 320 and 560 mg/kg, respectively), (8)(9)(10) crocin at different doses (50,200 and 600 mg/kg), (11-13), [11][12][13] safranal at different doses (0.05, 0.15, 0.35 ml/kg, respectively).…”
Section: Anxiety and Insomniamentioning
confidence: 99%
“…[6] Regarding saffron's pharmacological properties and possible therapeutic uses, several reviews and minireview papers have been published concerning the biological activity of saffron and its constituents. [1,3,[7][8][9][10][11][12][13][14] In parallel, the possible uses of saffron and its active constituents lead to an increasing number of research studies, some of which have drawn some very useful and intriguing results of active ingredients of saffron, especially against malignancies, cardiovascular and Alzheimer's disease. [15][16][17][18][19][20][21][22] In this minireview, we aim to summarize and critically address previous and current evidence regarding the biological/ pharmacological activities of saffron and its active ingredients and their possible therapeutic uses.…”
Section: Introductionmentioning
confidence: 99%
“…The C.sativus is widely used in Middle Eastern countries like Iran as spice, yellow dye and even a remedy [14]. Experimental investigations suggested that C.sativus has similar medicinal properties to other considered herbs in their studies [15][16][17]. It has been demonstrated that there is an antidepressant effect in its petal which cost plenty less compare to its stigma, so there is growing tendency to use.…”
Section: Introductionmentioning
confidence: 99%
“…However, alkaloids have long been existed before humans; some of them are structurally similar to neurotransmitters present in the central nervous system of humans. Considering the medicinal importance of alkaloids and research explaining their role in treating wild propagation of cells, they would be used as an effective chemopreventive agent in the era of modern drug innovation (63,64). Amaryllidaceae alkaloids, betalain alkaloids, diterpenoid alkaloids, indole alkaloids, isoquinoline alkaloids, lycopodium alkaloids, monoterpene and sesquiterpene alkaloids, peptide alkaloids, pyrrolidine and piperidine alkaloids, pyrrolizidine alkaloids, quinoline alkaloids, quinolizidine alkaloids, steroidal alkaloids, tropane alkaloids, and miscellaneous alkaloids are the main categories of Alkaloids.…”
Section: Alkaloidsmentioning
confidence: 99%